Determination of Some Heavy Metals in Selected Cosmetic Products Sourced from Wambai Market, Kano (CaJoST, 2025)
Heavy metals have a negative impact on both the environment and living things. It is well recognized that heavy metals are non-biodegradable, persistent, and difficult to remove. Intentionally, some of these heavy metals are added to cosmetics as pigments, additionally, there are a number of unintended ways that heavy metals contaminate cosmetics; raw materials, additives, color minerals and untreated water. This study was carried out to determine the contamination of heavy of lead, cadmium, chromium, and nickel, in some cosmetic products from Wambai Market and then evaluate their potential health effects. Cosmetic samples were digested using a standard method. Approximately 1.0 g of each sample was digested, diluted, and analyzed using an Atomic Absorption Spectrophotometer (AAS). Calibration curve for each metal was constructed using standard solutions to determine metal concentrations in the samples. A cross-sectional survey was conducted among female students residing at the old campus hostels of Bayero University, Kano. A structured questionnaire assessed their knowledge, practices, and perceptions regarding heavy metal contamination in cosmetics. Data were collected and analyzed using descriptive statistics.The AAS analysis revealed that cadmium and nickel concentrations in all samples were within acceptable limits (0.005 mg/L and 0.02 mg/L, respectively). However, lead concentrations in all samples exceeded the safe limit (0.01 mg/L). Chromium concentrations were within acceptable limits (0.05 mg/L) for all samples except Sample ML (38.53% RSD). This study revealed significant lead contamination in cosmetic products from Wambai Market, posing potential health risks to consumers.